Kajian Yuridis terhadap Hak Waris Anak yang Lahir di Luar Perkawinan: Studi Kasus Putusan MK NO. 46/PUU-VIII/2010 - Zahwa Alhabsyi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Significant developments in legal protection for illegitimate children occurred following the issuance of Constitutional Court Decision No. 46/PUU-VIII/2010. This decision opened the way for the recognition of legal relations between illegitimate children and their biological fathers, provided that this can be proven through scientific and technological approaches and legally valid evidence. Using normative research methods with statutory, case-based and conceptual approaches, this study analyzes the implications of this decision on the inheritance rights of illegitimate children under the Civil Code. The results indicate that legal protection for children born out of wedlock in inheritance is realized through two main instruments: preventive legal protection and repressive legal protection. Although the Constitutional Court Decision opened access to civil relations between illegitimate children and their biological fathers, Article 863 of the Civil Code, which limits the inheritance portion of illegitimate children, has not been amended, thus structural discrimination persists.